Kajian Interaksi Obat pada Pasien Gagal Jantung Di RSUD Abdul Wahab Sjahranie Kota Samarinda - Yolanda Pratiska; Risna Agustina; Rolan Rusli (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
Cardiovascular diseases is first cause of death and heart failure is the end of all heart diseases and heart failure is causative factor enhancement of mortalities and morbidities heart failure patient. The purpose of the research is to know drug interaction in heart failure patient who undergoing hospitalization in RSUD Abdul Wahab Sjahranie in Samarinda. This research is non experimental and use retrospective to take a material during periods January – December in 2018. The result analyzed use descriptive evaluative and show heart failure case more suffer to the men (59.25%) at age 55-65 (35.80%) with the most of level education is senior high school (39.50%). The studies showed 163 drug interaction case with 18 (11.04%) minor interaction, 140(85.88%) moderate interaction and 5 (3.06%) major interaction.